Implementasi Ruang Terbuka Hijau di Kecamatan Samarinda Ulu Berdasarkan Perda No. 7 Tahun 2023 - Fitriah, Sabriena Adilla; Suhadi, Nainuri (International Journal of Politic, Public Policy and Environmental Issues, 2024)
Green Open Space (RTH) plays a crucial role in creating a healthy and sustainable urban environment; however, the Samarinda Ulu District in Samarinda City faces challenges in meeting the RTH standards set by Law No. 26 of 2007 and the Samarinda City Regional Regulation No. 7 of 2023. This study aims to analyze the implementation of the Spatial Planning of RTH, identify the challenges faced, and provide recommendations to enhance the effectiveness of RTH management. The research employs a normative approach, collecting data through literature studies, interviews, and field observations. The findings indicate that out of the targeted 30% RTH, the Samarinda Ulu District has only achieved approximately 0.4393%, with the main challenges being land limitations, a lack of competent human resources, and low community participation. Collaborative efforts between the government and the community are essential to raise awareness of the importance of RTH, along with intensive education and outreach to realize optimal RTH for improving the quality of the environment and the well-being of the community.